Early life body size and its associations with adult bladder cancer - Kathrine K. Sørensen; Britt W. Jensen; Peter E. Thomas; Kirsten Madsen; Frank Eriksson; Julie Aarestrup; Jennifer L. Baker (Taylor & Francis Group, 2020)
Background: Adult overweight is a potential bladder cancer (BC) risk factor, but little is known about size earlier in life. Aim: To investigate if birth weight, childhood body mass index (BMI), height and growth are associated with adult BC. Subjects and methods: Anthropometric information from birth and ages 7-13 on 315,763 individuals born 1930-1989 in the Copenhagen School Health Records Register was linked to national registers. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated by Cox regression. Results: 1145 individuals (839 men) were diagnosed with BC. Sex differences were not detected. Childhood BMI had positive associations and height had inverse associations with BC; at age 13, HR = 1.10 (95% CI: 1.02-1.18) per BMI z-score and HR = 0.94 (95% CI: 0.89-1.00) per height z-score. A pattern of above-average increases in BMI from 7 to 13 years had higher hazards of BC than average increases. Above-average growth in height was not significantly associated with BC. Compared with birth weights of 3.5 kg, low (2.5 kg) and high (4.5 kg) values were associated with increased hazards of BC; HR = 1.26 (95% CI: 1.01-1.58) and HR = 1.36 (95% CI: 1.09-1.70), respectively. Conclusions: A high BMI, a short height, excess BMI gain in childhood and low and high birth weights are associated with increased hazards of BC.